PENGEMBANGAN MODUL ELEKTRONIK KIMIA MATERI ASAM BASA SMK MENGGUNAKAN APLIKASI 3D PAGE FLIP CORPORATE EDITION - Yusa Malinda, Friesca; Elvinawati, Elvinawati; Amida, Nadia (ALOTROP, 2024)
This study aims to determine the feasibility and response of students to the developed electronic chemistry module. This development study was adapted from the Borg and Gall me development model which used 7 out of 10 stages which were limited to the product revision stage. The data of this study were obtained from interviews, material and media expert validation questionnaires, student response questionnaires on small-scale product trials. The results of material expert validation showed that the electronic chemistry module developed obtained an average percentage of 85.73% while the results of media expert validation obtained an average percentage result of 87.06% which was in the range of 84% < V 100% with the criteria very valid. In a small-scale product trial to determine student responses to the developed chemistry electronic module, the average percentage of 83,38% % in the range of 68% < V 84% in the good category. It can be concluded that the electronic chemistry module developed in this study is suitable for use as chemistry teaching materials for class X SMK students. Keywords: Chemical Electronics Module, Page Flip Corporate Editions, Acid Base